Analysis of Holbung Hill Tourism Development Strategy for Improving Regional MSMEs - Franika BR Manjorang; Liliana Dewi (Budapest International Research and Critics University, 2022)
Holbung Hill is one of the natural beauties in North Sumatra, especially Samosir Island. This hill is often referred to as the North Sumatra version of Tele tubbies hill become a tourist area. This study aimed to analyze the development strategy of Bukit Holbung tourism in increasing regional MSMEs. The method used in this research is descriptive qualitative method with descriptive type. The technique of determining information is carried out by observation, namely collecting data and presenting the obtained data, which is then carried out by drawing conclusions. The results of the analysis show that the government as well as the community must be involved in the development of Bukit Holbung. Especially the people of Hariarapohan Village. In supporting the development of Bukit Holbung tourism, it is necessary to improve the inadequate infrastructure to increase MSMEs in the Bukit Holbung area.